Clustering with Multi view point-Based Similarity Measure using NMF - P.Krishnakumari, R.Saranya (International Journal of Scientific Research and Management (IJSRM), 2013)
Clustering is the one of the major important task in data mining .The task of clustering is to find the fundamental structures in data and categorize them into meaningful subgroups for supplementary study and examination. Existing K-Means clustering with MVS measure it doesn't best position to cluster the data points. This problem will lead to gain less optimal solution for clustering method. This paper presents a solution to the Mulitview point based similarity measure with NMF clustering to predict k value. This paper gives a detailed study on proposing the multiview point clustering approach with the NMF clustering method. Finally experimental result were compared with the parameters in terms of precision and recall to measure the accuracy of the MVS and NMF clustering.